PEMANFAATAN LIMBAH RUMAH TANGGA SEBAGAI ALAT OLAHRAGA TRADISIONAL KEPADA REMAJA RT013 KELURAHAN TELUK PUCUNG - Ahmad Fauzan Abdurrahim; Hasan Basri; Adli Azhari (Universitas Islam 45 Bekasi, 2022)
Many waste materials from housing, trade buildings, offices and similar facilities can be utilized and processed into something of value, including by utilizing wood waste as a traditional sports tool for beam running. Teenagers as the next generation must of course continue to innovate and work real for the greatness of the Indonesian nation. However, nowadays many teenagers who still do not get a job then become unemployed. The existence of this activity aims to invite teenagers to fill their spare time with positive and useful activities, namely by utilizing wood waste as a traditional sports tool for beam running. In addition to filling spare time, this activity is also useful for increasing economic empowerment, as well as increasing stimulus.